Digital Transformation in Accounting: Opportunities and Challenges in the Industry 4.0 Era - Harianto, Dedi (Outline Journal of Management and Accounting, 2025)
Digital transformation brings significant changes in accounting practices, especially in improving the quality of financial information. This study aims to analyze the impact of digitalization on the quality of financial reporting through a literature review approach. The quality of information in question includes relevance, reliability, and timeliness. The study's results indicate that technologies such as ERP, cloud accounting, big data, and blockchain contribute to process efficiency and enhanced reporting transparency. However, the implementation of technology still faces challenges, such as limited digital literacy, human resource readiness, and a lack of regulation, particularly in the MSME sector. Using the theoretical frameworks of Resource-Based View, Information System Success Model, and Institutional Theory, this article concludes that the success of digital transformation in accounting heavily depends on the synergy between technology, user competencies, and supportive policies. These findings are expected to contribute to the development of more adaptive and sustainable digital accounting strategies.